Pengaruh Variasi Kecepatan Pendingin dan Kecepatan Ekstrusi Terhadap Dimensi dan Kepadatan Filamen Produk Mesin Plastik Single Screw Extruder - Muhammad Salman Nasyirudien; Bambang Irawan; Subagiyo Subagiyo; Vinan Viyus (International Forum of Researchers and Lecturers, 2025)
This study analyzes the effect of variations in cooling and extrusion speeds on a single screw extruder plastic machine to produce filaments. The method used is a factorial Design of Experiment (DOE) with a two-way ANOVA test, where the cooling speed (8.7 m/s, 11.8 m/s, 14.3 m/s) is varied using the inlet valve on the blower and extrusion (20, 30, 40 rpm) is varied using a tachometer. The testing process includes measuring the dimensions and weighing the filament after the extrusion process, and the data is processed using Excel and Minitab-21. The results show that increasing the cooling speed decreases the dimensions and density of the filament, while increasing the extrusion speed increases the dimensions and density of the filament. The interaction between the two is also proven to be statistically significant with 0.000 on dimensions and 0.014 on density ≤ 0.05 (p-value ≤ 0.05). The optimizer response determined the optimal combination at a cooling speed of 14.3 m/s and an extrusion speed of 20 rpm for a target dimension of 1.75 mm, while the optimal parameters for density were at a cooling speed of 8.7 m/s and an extrusion speed of 40 rpm, resulting in the highest density of 0.246 g. These recommendations are expected to improve the efficiency and quality of filament production.